2020
DOI: 10.7554/elife.59212
|View full text |Cite
|
Sign up to set email alerts
|

Poultry farmer response to disease outbreaks in smallholder farming systems in southern Vietnam

Abstract: Avian influenza outbreaks have been occurring on smallholder poultry farms in Asia for two decades. Farmer responses to these outbreaks can slow down or accelerate virus transmission. We used a longitudinal survey of 53 small-scale chicken farms in southern Vietnam to investigate the impact of outbreaks with disease-induced mortality on harvest rate, vaccination, and disinfection behaviors. We found that in small broiler flocks (≤16 birds/flock) the estimated probability of harvest was 56% higher when an outbr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…Overrepresentation of disease is possible in slaughterhouse populations such as this one. For example, Vietnamese poultry smallholders were reported to increase their sales to mitigate losses associated with an outbreak (39). No lesions of any stage were observed during this study, and it is unlikely that all shedding cattle were in the pre-clinical stages of FMD.…”
Section: Discussionmentioning
confidence: 84%
“…Overrepresentation of disease is possible in slaughterhouse populations such as this one. For example, Vietnamese poultry smallholders were reported to increase their sales to mitigate losses associated with an outbreak (39). No lesions of any stage were observed during this study, and it is unlikely that all shedding cattle were in the pre-clinical stages of FMD.…”
Section: Discussionmentioning
confidence: 84%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License about 29 million (Padhi, 2016), of which 75% are indigenous chickens (Delabouglise et al, 2020). Kamau et al (2018) observed that 80% of the poultry production originates from smallholders with 7.1 and 9.4% of meat and egg products originating from indigenous chickens, respectively.…”
Section: Introductionmentioning
confidence: 93%
“…Besides, increase in prices of poultry products has reduced consumption among low-income rural families to about 7% (Goraga et al, 2018). This is so despite poultry being a key contributor to economic development and vital towards achieving the socio-economic pillars of Vision 2030 (Delabouglise et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the 2014/2015 H5N2 outbreak in the USA resulted in the death or culling of over 50 million poultry, and was estimated to have a negative economic impact of over $3 billion ( 30 ). In low income countries, financial implications can drive smallholder poultry farmers to respond to poultry deaths by rapidly selling stocks, often at markets, which does not help with containment of emerging viruses ( 31 ). Despite the obvious benefits of vaccinating poultry in terms of biosecurity, routine vaccination of poultry has cost implications, which means that flock depopulation is a more cost-effective control strategy in many countries ( 32 , 33 ).…”
Section: Avian Influenza Virusesmentioning
confidence: 99%